Characteristics and Risk Factors of Cytokine Release Syndrome in Chimeric Antigen Receptor T Cell Treatment - Yan, Zhiling; Zhang, Huanxin; Cao, Jiang; Zhang, Cheng; Liu, Hui; Huang, Hongming; Cheng, Hai; Qiao, Jianlin; Wang, Ying; Wang, Yan; Gao, Lei; Shi, Ming; et al. (Frontiers in Immunology, 2021)
Clinical trials have confirmed that chimeric antigen receptor (CAR) T cell therapies are revolutionizing approaches for treating several relapsed or refractory hematological tumors. Cytokine release syndrome (CRS) is an adverse event with high incidence during CAR-T treatment. A further understanding of the characteristics and related risk factors of CRS is important for the effective management. 142 patients with relapsed or refractory acute lymphocyte leukemia (ALL), lymphoma or multiple myeloma (MM) received lymphodepletion chemotherapy followed by infusion of CAR-T cells. The characteristics of CRS at different time points after treatment were monitored and risk factors were analyzed. The incidence of CRS for ALL, lymphoma and multiple myeloma were 82%, 90% and 90% respectively. Fever was observed on a median of day 3 for ALL, day 1 for lymphoma, and day 8.5 for MM after CAR-T cell infusion and the duration was different between grade 1-2 CRS and grade 3-5 CRS. Disease types, co-stimulatory molecules, peak concentration of IL-6 and CRP were associated with independent risk factors for grade 3-5 CRS. For patients with ALL, numbers of lymphoblast in bone marrow before lymphodepletion , peak concentration of IL-6 and CRP were independent risk factors of CRSwas different between patients without CRS and those with CRS. Clinical stage of lymphoma patients and high tumor burden in marrow of MM patients were independent risk factors of CRS. Prior-hematopoietic stem cell transplantation, the number of lymphoblasts in bone marrow before lymphodepletion, and the derivation of CAR (humanizing or mouse) were independent risk factors of grade CRS. In conclusion, the characteristics and risk factors of CRS in different B-cell hematological tumors are different and should be managed individually during CAR-T cell therapy.